Improving Services To Communities In Pringsewu District Goverment With E-Government Concept - Satria Abadi; Diono Supatno (Komunitas Dosen Indonesia, 2018)
The dynamics of the development of information technology that occurred in the global era as it is now has changed many of the procedures of various organizations in its management, both profit-oriented and non-profit-oriented organizations, especially government organizations. Providing good service to the wider community is one of the triggers. to improve performance in the government operating system concerned. This performance improvement leads to services that are more quality, faster, and easier. The development in the field of information technology is a facility to implement management of government organizations electronically or electronic government (e-government). In general, e-government practices in Indonesia have not been strategically positioned or only limited to supporting programs. On the other hand, building a government site has already begun to be carried out, as a form of the application of the concept of e-government, although in Indonesia it has generally only entered the level of interaction. One thing that needs to be considered in the presentation of the site is the consistency of information, so that it can anticipate the emergence of public doubts about the credibility of the government as a site presenter. Many problems are still being faced to better empower e-government as it should. The hardest problem is resistance to change, where certain parties in the government still maintain an old culture that tends to be bureaucratic. This problem must be overcome so that the concept of e-government can be applied and empowered to provide the best service to the wider community.